Accounting Vouchers and Principles of Bookkeeping : Expectations in 21st Century - Olszewska, Irena; Wołczyńska, Monika (World Bank, Vienna, 2016)
The current regulations and practices related to accounting vouchers and bookkeeping in Poland, including cross-cutting tax regulations, were assessed and compared with selected EU countries (France, Germany and UK). The study was undertaken at the request of the Polish Ministry of Finance, and funded under the Financial Reporting Technical Assistance Program (FRTAP), to contribute to efforts to enhance harmonization with other relevant regulations, reduce unnecessary requirements and red tape for entities (especially SMEs and micro entities), and to reflect current and potential future technology changes whilst retaining control over diligence and quality of bookkeeping. The content, quality and scope of legislation in this area was found to be generally good. In contrast to the other countries studied, however, it takes a detailed, prescriptive approach. The report suggests moving away from setting detailed requirements and towards the development of a clear general framework. This would help preserve the quality of bookkeeping and accounting practices but reduce the need for continuous amendments to regulations to keep pace with changing circumstances, for example technological changes. It would also create space for more liberalization and greater flexibility for market practitioners and would be in keeping with the approach adopted in the other countries looked at. The report identifies gaps and inconsistencies in the areas of accounting policy and maintenance of books; accounting vouchers; financial statements; storage; provision of bookkeeping services; and information technology (IT) and makes a number of suggestions to address these.